The discovery of Trypanosoma cruzi and Chagas disease (1908-1909): tropical medicine in Brazil A descoberta do Trypanosoma cruzi e da doença de Chagas (1908-1909): medicina tropical no Brasil - Simone Petraglia Kropf; Magali Romero Sá (História, Ciências, Saúde: Manguinhos)
This article analyzes the discovery of Chagas disease and the parasite that causes it (Trypanosoma cruzi) by Carlos Chagas in 1908/1909, with a special focus on the scientific and social context in which this occurred. Its inclusion in the international debate on European tropical medicine - especially with researchers from the German school of protozoology - and its connection with discussions on the modernization of the recently established Brazilian Republic are also examined. The discovery of Chagas disease became a decisive aspect in the scientific project that Oswaldo Cruz sought to establish at the institute that bears his name. It was extolled as a symbol of Brazil's scientific ability to produce knowledge in line with the international scientific agenda, while simultaneously being attuned to the specific problems of the country. Analisa o contexto científico e social da descoberta, por Carlos Chagas, em 1908/1909, da doença que leva seu nome, bem como do Trypanosoma cruzi, parasito que causa esta enfermidade. Examina sua inserção no debate internacional da medicina tropical - especialmente com pesquisadores da escola alemã de protozoologia - e nas discussões sobre a modernização brasileira. A descoberta foi decisiva ao projeto de ciência que Oswaldo Cruz pretendida erigir no Instituto de Manguinhos. Foi enaltecida como símbolo da capacidade da ciência nacional em produzir conhecimentos afinados com a agenda científica internacional e, ao mesmo tempo, relacionados aos problemas específicos do Brasil.